SEATROBS: Requirements and Design For Sealife Travel & Tour Online Booking System Using Usability Theory - Mazita, Mokhtar; Nor Hasnul Azirah, Abdul Hamid; Nurul Athirah, Ahmad Nazri (2021)
The travel and tour industry is one of the world's largest industries with such a phenomenal target audience base, where businesses in this industry always seek advanced technology to face intense competition. Sealife Travel and Tour Sdn. Bhd. is one of them where the owner of this company is seeking a system that can cater to the problems faced by them due to the implementation of a manual system in the customers' booking process. The first problem is exchanging information between the staff and customers through call and WhatsApp, resulting in miscommunication between them and the paper-based system that is prone to loss, misplaced, and less secure. The biggest downfall for Sealife Travel and Tour Sdn. Bhd. is the amount of space that is used to store all the customers' booking files. These problems bring inefficiency since most of the travel industry businesses worldwide are currently embracing the technologies for competitive advantages and providing better services to the customers. So, the aim of developing the Sealife Travel Online Booking System (SEATROBS) in this research paper is for helping the staffs of the company in managing the booking information of the customers. The Adapter Waterfall model has been used in developing this system. Additionally, usability heuristics had been used as a theory to guide the development of this system. The system has been tested with four (4) users and two (2) experts. The testing method used for the users is the ISO/IEC 9126-4 approach to measure the usability metrics that includes efficiency, effectiveness, and satisfaction. For the experts, heuristic evaluation is used that brings six (6) usability principles into implementation for testing. The result of the testing is very satisfying, as it shows 71.51% of efficiency, 83.33% of effectiveness and three (3) out of four (4) users very satisfied with the system. The result of heuristic evaluation also come out as successfully implemented. The details of the result are being discussed in this paper and expected to meet the specification of the users and ready to go live.